Comparative carotenoid compositions during maturation and their antioxidative capacities of three citrus varieties. (1st April 2016) - Yoo, Kyung-Mi; Moon, BoKyung
Highlights: Korean Citrus fruits were evaluated for their comparative carotenoid compositions. β-Cryptoxanthin, zeaxanthin, and β-carotene were the predominant carotenoids. β-Cryptoxanthin mainly affects the increase of carotenoids during maturation. Yuza variety exhibited high antioxidant activity, total carotenoids, and vitamin C. Lycopene, α- and β-carotene, and β-cryptoxanthin demonstrated high VCEAC values. Abstract: This study investigated total carotenoid content, comparative carotenoid composition, vitamin C content, and total antioxidant capacity of three citrus varieties which are Yuza ( Citrus junos Sieb ex Tabaka), Kjool ( Citrus unshiu Marcow), and Dangyooja ( Citrus grandis Osbeck). Seven carotenoids were identified, with β-cryptoxanthin, astaxanthin, and zeaxanthin being predominant in citrus varieties. Ripening increased the total carotenoid in three citrus varieties. Individual carotenoid of canthaxanthin, astaxanthin, and α-carotene in citrus varieties decreased with maturation, whereas the others increased with ripening. Yuza exhibited the highest total antioxidant capacity in 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assays, with VCEAC values of 582.9 mg/100 g and 451.5 mg/100 g, respectively. The relative VCEAC values were vitamin C (1.00) > lycopene (0.375), α-carotene (0.304), β-carotene (0.289), β-cryptoxanthin (0.242), and zeaxanthin (0.099). These results indicate that Yuza contains higher amounts of total carotenoids, individual carotenoids, and vitamin C than other Korean citrus varieties.